The US Chemical Safety Board: Moving forward to continually drive chemical safety change. Issue 4 (10th November 2016) - Sutherland, Vanessa A.
Abstract : Over the course of my first year as Chairperson's of the Chemical Safety and Hazard Investigation Board (CSB), I have overseen the release of several incident investigations, deployed to a number of accident sites, increased the CSB's outreach initiatives and evaluated our organizational processes to more effectively and productively achieve our critical mission. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 306–311, 2016